Characterization of grain boundary disconnections in SrTiO3 part II: the influence of superimposed disconnections on image analysis - Sternlicht, H; Rheinheimer, W; Kim, J; Liberti, E; Kirkland, A; Hoffmann, M; Kaplan, W (Springer Verlag, 2018)
Disconnections were recently shown to play a role in the mechanism of grain boundary motion in general grain boundaries in SrTiO3. In this work, we demonstrate the existence of disconnections in the viewing direction along the projected thickness of transmission electron microscopy samples and characterize possible aspects of the structure of these disconnections. We show that the presence of steps along the viewing direction may result in the appearance of a disordered region at the boundary, while it is actually composed of ordered crystalline material. We discuss the subsequent complications in analysis of transmission electron microscopy data and strict meaning of the term “edge-on” for grain boundaries.